Navigation of Hudson Bay and Straits [electronic resource] - Bell, Charles N. (Charles Napier), 1854-1936; Historical and Scientific Society of Manitoba. (Winnipeg : Manitoba Daily Free Press, 1883)
From: Manitoba Historical and Scientific Society Winnipeg. Transaction no. 1, Season 1883-4. Cover title. Appended: the author's Hudson's Bay country, a letter to the editor of the Free Press. "A paper read before the Society on the evening of 10th May, 1883." Electronic reproduction. Mode of access: Internet. 44